Analisis Proses Pemecahan Masalah Mahasiswa Calon Guru Matematika pada Soal Cerita melalui Perspektif Model Polya - Agusfianuddin Agusfianuddin; Ahmad Muzaki; I Ketut Sukarma; Ria Saputri (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
Solving word problems serves as an indicator of prospective mathematics teachers' critical thinking skills, specifically their ability to link contextual representations with mathematical models. However, in reality, many prospective mathematics teachers are not yet accustomed to using problem-solving models, such as Polya’s model. This study aims to analyze the problem-solving processes of prospective mathematics teachers when solving word problems, viewed through the lens of Polya’s model. Polya’s model comprises four stages: understanding the problem, devising a plan, carrying out the plan, and looking back (reviewing the results). This is a qualitative descriptive study employing a case study design. The subjects consisted of 60 students from the Mathematics Education Study Program at Mandalika University of Education, drawn from various semesters. Purposive sampling was used to select participants based on high, medium, and low ability categories. Data collection involved source triangulation using tests, questionnaires, interviews, and documentation in the form of teaching practice videos. Subsequently, the data were analyzed using a qualitative descriptive approach. The results indicate that while students could identify the given information and the questions asked, they tended not to write them down. Students demonstrated competence in the "carrying out the plan" stage but showed weaknesses in the "devising a plan" and "looking back" stages. These findings highlight the need to strengthen conceptual understanding, systematic thinking skills, metacognitive abilities, and the capacity to solve non-routine problems, as well as to provide training in reflective thinking, so that prospective teachers can apply Polya’s model more comprehensively in mathematical problem-solving. The study's findings are expected to serve as a basis for reflection for educators and prospective educators regarding the importance of incorporating problem-solving model procedures into the learning process.